Sonic velocity discontinuity for CO2 brine mixtures in the context of carbon storage in aquifers - Norouzi, Amir Mohammad; Paydayesh, Mehdi; Ireland, Mark; Babaei, Masoud (Frontiers in Earth Science, 2026)
Accurate modelling of fluid acoustic parameters and saturation distributions in heterogeneous aquifers is essential for predicting CO2 plume behaviour. Conventional approaches, such as Batzle & Wang’s (1992) equations, fail to capture the complexities of CO2–brine interactions under reservoir conditions. In this paper, we apply thermodynamic modelling to calculate sonic velocity and density of CO2–brine mixtures, addressing the applicability of conventional averaging bounds for mixture bulk modulus. Results show that for low CO2 mole fractions (xCO2≤0.1−0.2), mixture properties remain relatively constant and sonic velocity follows the Gassmann-Hill bound. However, a discontinuity occurs at mole fractions of 0.1–0.2, where sonic velocity shifts to the Gassmann-Wood bound, driven by a sudden density drop as CO2 patches form. Importantly, values lower than the harmonic bound are observed, consistent with Landau–Lifshitz’s theorem. Based on the results of this study, we demonstrate that the sonic velocity discontinuity coincides with the two-phase boundary between the CO2 plume and brine. At low CO2 mole fractions, dissolved gas slightly increases mixture density, but beyond ∼0.2 mole fraction, brine evaporation into CO2 causes a sharp density decrease. This behaviour implies that monitoring sonic velocity discontinuities provides a practical means to detect CO2 dispersion within aquifers, thereby improving seismic interpretation accuracy in storage projects.